A multi-staged neuropeptide response to traumatic brain injury - Alves, José Luís (2020)
As the most abundant neuropeptides in Central Nervous System, Substance P and Neuropeptide Y are arguably involved in the response to brain trauma. This study aims to characterize a new concept of multi-staged neuropeptide response to TBI.